Scaling Your Node.js Apps Progress Your Personal Projects to Production-Ready - Doglio, Fernando (Apress, 2018)
Take your Node.js application into production-ready status, capable of scaling up to whatever your needs might be. You'll discover that architecting for successful, popular sites is an essential tool of any professional Node.js developer, and learning to scale your own applications is a great place to start. Using this book you will learn when to scale, what factors should trigger scaling, and what architectural techniques are best suited for scaling. You will also explore common pitfalls that arise when scaling a Node.js application and solutions to correct them. Including analyses of success cases at the largest-scale companies, such as Netflix and Paypal, this book will get you started with scaling in no time at all.